2010
DOI: 10.1002/pds.1924
|View full text |Cite
|
Sign up to set email alerts
|

Validation of claims‐based diagnostic and procedure codes for cardiovascular and gastrointestinal serious adverse events in a commercially‐insured population

Abstract: The results suggest that, for certain adverse events, claims data can serve as the basis for pharmacoepidemiology research and drug safety surveillance in the US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 13 publications
6
117
1
Order By: Relevance
“…Disease surveillance and quality‐of‐care studies frequently use information from administrative claims databases, such as Medicare, by identifying patients with specific conditions based on International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) codes. Studies comparing the accuracy of ICD‐9‐CM codes with medical record review find variations in agreement depending on code selection,2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 as well as patient characteristics, such as age, race/ethnicity,10, 11 sex,11 and length of hospitalization 3. Aside from teaching hospital status10 and hospital departments,16 potential variations in accuracy based on other hospital characteristics are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Disease surveillance and quality‐of‐care studies frequently use information from administrative claims databases, such as Medicare, by identifying patients with specific conditions based on International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) codes. Studies comparing the accuracy of ICD‐9‐CM codes with medical record review find variations in agreement depending on code selection,2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 as well as patient characteristics, such as age, race/ethnicity,10, 11 sex,11 and length of hospitalization 3. Aside from teaching hospital status10 and hospital departments,16 potential variations in accuracy based on other hospital characteristics are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, high specificity of the outcome is preferable to high sensitivity, as the relative risk estimates are unbiased when specificity approaches 100% [123]. It has been shown that claims data can identify cardiovascular endpoints with very high specificity, resulting in relatively small potential for bias associated with misclassification of the outcome [124][125][126][127][128]. Among the evaluated literature, few explorative analyses assessed the potential effect of outcome misclassification on the study estimates [68,70].…”
Section: Other Issuesmentioning
confidence: 99%
“…The PPV of this algorithm is 86%, which is comparable to other peer-reviewed algorithms. 16 Other bleeding was defined as genitourinary bleeding, hemopericardium, hemoperitoneum, hemarthrosis, epistaxis, hemoptysis, hemorrhage from throat, and unspecified hemorrhage. 15 Ischemic stroke was defined based on the presence of ICD-9-CM codes 434.xx (occlusion of cerebral arteries) and 436.xx (acute but illdefined cerebrovascular disease) as the primary discharge diagnosis in any inpatient claim following the index date.…”
Section: Definition Of Outcomesmentioning
confidence: 99%